Empowering Santripreneur through Catfish Farming Based on Asset-Based Community Development at Pesantren Al-Hijrah - Sinaga, Sopian; Simbolon, Nur Rafidah Mahdiyyah; Dea Alfina; Asma Sahira; Hidayani; Wita Siti Maryam; Nur Hafizah (ASSUNNAH PRESS, 2025)
Islamic boarding schools (pesantren) play a strategic role in fostering santripreneurship by integrating religious values with entrepreneurial skills to achieve economic independence. Pesantren Al-Hijrah owns 2,000 m² of waqf land and an idle fish pond; however, limited knowledge and skills in catfish farming hinder the utilization of these assets. This community service program aimed to enhance the knowledge and skills of santri and teachers in catfish farming and to optimize pesantren assets for economic empowerment. The program was conducted from March 2–17, 2025, involving 13 santri and four teachers, using an action research design with an Asset-Based Community Development (ABCD) approach through four stages: Discovery, Dream, Design, and Destiny. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed descriptively. The results show a significant increase in participants’ competencies, with 100% able to explain the stages of farming, 94% able to select high-quality fingerlings, 88% able to master feeding and disease control, and 82% able to understand marketing strategies. Technical skills improved, with full participation in pond preparation and stocking, while entrepreneurial motivation reached 88%. Pesantren assets were successfully activated through the productive utilization of ponds and the strengthening of local practitioner networks. The ABCD approach proved effective in empowering santri and teachers toward sustainable santripreneurship. Continuous mentoring and institutional partnerships are recommended to ensure program sustainability.